Increasing Access to Science and Engineering-the Role of Multimodality - John Airey; Zachary Simpson (Stockholm University Press, 2019)
The idea for this special issue of 'Designs for Learning' emerged during the 8th International Conference on Multimodality (8ICOM), held in Cape Town in December 2016. During that conference, a special stream of papers was organised, all of which addressed the question of science and/or engineering teaching from a multimodal perspective. In this editorial we discuss the issue of multimodal access to science and engineering and introduce the papers in the special issue.